Association between Oral Health Literacy and Socioeconomic Variables in Users of Centers for Dental Specialties - Alcir José de Oliveira Júnior; Fábio Luiz Mialhe; Eduardo de Novaes Benedicto; Maria Ercília de Araujo; Mariana Gabriel (Association of Support to Oral Health Research (APESB), 2021)
Objective: To test possible associations between Oral Health Literacy (OHL) level and socioeconomic covariates among users of Centers for Dental Specialties (CEOs). Material and Methods: The Health Literacy in Dentistry (HeLD-14) instrument was applied to 130 adult users of CEOs located in 13 municipalities in the state of São Paulo - Brazil, as well as socioeconomic issues. The researcher applied instruments in a specific room after randomly selecting individuals in the waiting room and invitation acceptance. Each item was ranked on a 5-point scale, ranging from 0 to 4, in which high scores indicate minimal difficulties in performing functions (high OHL) and low scores indicate very limited abilities to perform functions (low OHL). Statistical analysis using the Levene test was used to verify the possibility of using the one-way ANOVA test, and in case results show positive values (p>0.05), the Kruskal Wallis test was used. Results: The average age of participants was 45 years, with more than half being female (68.7%) with 9-11 years of schooling (48.4%). When considering the total value of HeLD-14 questions, OHL was associated with covariates schooling, marital status and family income. Conclusion: OHL levels were associated with socioeconomic variables, contributing to evidence in this field of specialized care.